Metastatic ovarian carcinoma one year after surgical removal of colon carcinoma during pregnancy: a case report. (1st January 2006) - Gurbuz, A.; Kir, G.; Karateke, A.; Haliloglu, B.; Kabaca, C.
Abstract : Colorectal carcinoma during pregnancy is a very rare event. We presented a woman with metachronous metastatic ovarian tumor existing 1 year after surgical removal of perforated sigmoid colon carcinoma encountered during cesarean section of woman of 36-week gestation for fetal distress. Pregnant women with suspicious abdominal mass should be evaluated for a possible colorectal carcinoma even in the absence of any other gastrointestinal symptoms associated with it and undergo rectal examination and sigmoidoscopy. In addition, as synchronous and metachronous ovarian metastases are common in these patients, ovaries must be evaluated carefully by bisection during operation for possible metastasis, and in women who do not have a desire for fertility, prophylactic oophorectomy seems an appropriate treatment modality for resecting synchronous metastasis and preventing future metastasis.